CINEMA AS A SYMBOL OF MODERNITY IN TERESINA (1900-1920) - Peron Cunha Carvalho, Isaac (Revista Gênero e Interdisciplinaridade, 2022)
This paper aims to analyze the cinema as a symbol of modernity in Teresina, Piauí from 1900 to 1920, with emphasis on the study of the context in which the city was going through at the time, which underwent several transformations, both daily, as social and economic, with the insertion in society of several technological innovations, establishing immediate relations with the big cities. In this way, historiographic texts that explain the concept of city were used, such as Raquel Rolnik, Sandra Jatahy Pesavento, Roberto Lobato and Michel de Certeau. Also used were texts that elucidate about the modernization process, such as the texts by Nicolau Sevcenko, Francisco Alcides do Nascimento, and Teresinha Queiroz.